Triclosan Caused Oocyte Meiotic Arrest by Modulating Oxidative Stress, Organelle Dysfunctions, Autophagy, and Apoptosis in Pigs - Ning Zhao; Anli Xu; Jingxian Yang; Jianan Zhao; Junhao Xie; Bugao Li; Jiaxin Duan; Guoqing Cao (Animals)
Triclosan (TCS) is a highly effective broad-spectrum antibacterial agent; however, the specific roles of TCS in oocyte maturation remain poorly understood. This research investigated the influence of TCS on biologically active processes during the in vitro maturation of porcine oocytes. Our results demonstrated that TCS significantly decreased the maturation rate of porcine oocytes in a concentration-dependent manner and impaired cumulus expansion. These detrimental effects were mediated by the disruption of mitochondrial function and distribution, leading to oxidative stress characterized by an accumulation of reactive oxygen species (ROS), a decrease in the expression of the antioxidant enzymes SOD2 and GSH, reduced ATP production, and a loss of mitochondrial membrane potential (ΔΨm). We also observed interference with endoplasmic reticulum (ER) distribution, disturbances in Ca2+ homeostasis, and fluctuations in ER stress, as evidenced by reduced expression of ER stress-related proteins. Furthermore, TCS exposure induced autophagy, as indicated by the levels of SQSTM1 (P62) and LC3-II. Additionally, TCS increased apoptosis rates, corresponding with a downregulation of Bcl-2 expression. Collectively, our findings suggest that exposure to TCS can impair cytoplasmic function, thereby affecting oocyte quality.